Building Bonding and Bridging Capital through the 'China Club'. Issue 3 (3rd July 2018) - Santoro, Ninetta; Cassidy, Claire; MacDonald, Craig
Abstract: Out-of-school activities offered to young people can be discrete activities, completely divorced from school life and school curriculum, or they can offer extensions to normal school curriculum. This article reports on an ethnographic case study that investigated the effectiveness of a particular out-of-school activity, the 'China Club'. It offered secondary school pupils in the West of Scotland opportunities to learn about Mandarin language and Chinese culture, and facilitated the development of Bonding Capital between the group members and Bridging Capital between individual group members and people outwith the group. In working with those with whom they would not normally have engaged, and in visiting China as part of the 'China Club', the young people's peer relationships were positively impacted upon, as was their willingness to take risks by moving beyond familiar and predictable social and learning environments to those that challenged and tested them, socially, and as learners.